Students' Difficulties in Online Learning of English Subject during Covid-19 Pandemic: A Case at SMPN 3 Satu Atap Karangsambung - Kisi Pangestuti; Basuki Basuki; Juita Triana (Scripta : English Department Journal, 2022)
The purpose of this study is to find out the difficulties faced by students when studying English in an online school and the solutions they use to overcome those difficulties. The objective of this descriptive qualitative research is to explain the real situation of eighth grade students' learning problems at SMPN 3 Satu Atap Karangsambung, with the researcher as the key instrument. Researchers used the WhatsApp application to disseminate a questionnaire and conduct interviews with respondents in order to collect data. In analyzing the data, the researcher detects and categorizes learning difficulties, displays and calculates the percentage of data using the original text in the form of an essay, and provides findings and recommendations after evaluating the data. The study's findings revealed five challenges that students face when studying English in an online education setting. The most common issue students have is increasing English vocabulary, which has an impact on the appearance of the other four obstacles. In addition, the majority of students utilized the same approach to overcome their learning difficulties, according to the findings. The findings of this study aid teachers in assessing the learning process in order to better meet the needs of students.